Kit Messham-Muir: ’Claudia Parducci: The Space Between Us’, 2015 - Messham-Muir, Kit (StudioCrasher, 2015)
Contemporary artist Claudia Parducci spent two years developing a body of work for an exhibition called The Space Between Us, which opens in Ochi Projects, Los Angeles in January 2016. This documentary looks at the development of her ideas and work leading up to the exhibition. Dr Kit Messham-Muir The University of Newcastle